2010
DOI: 10.1021/jf100471n
|View full text |Cite
|
Sign up to set email alerts
|

Enterodiol and Enterolactone Modulate the Immune Response by Acting on Nuclear Factor-κB (NF-κB) Signaling

Abstract: Lignan-rich whole-grain cereals, beans, berries, and nuts show protective effects against a variety of chronic diseases, including cancer. Lignans are converted by intestinal microflora to enterolactone (EL) and its oxidation product enterodiol (ED). To investigate the immunomodulatory effect of EL and ED in human cells, peripheral blood lymphocytes were treated with increasing physiologically relevant concentrations of EL and ED (0-1000 microM) and stimulated with lipopolysaccharide (LPS) and anti-CD3 plus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 40 publications
0
44
0
Order By: Relevance
“…These levels of bioavailable metabolites can exert modulatory effects in cells through selective actions on different components of the intracellular signaling cascades, which are vital for cellular functions such as growth, proliferation, and apoptosis (Crozier et al, 2009;Corsini et al, 2010). Therefore, the concentrations used in the present study (10 mm/l) are physiologically relevant (Corsini et al, 2010). In addition, the metabolism and tissue distribution of enterolactone as well as its enterohepatic circulation (Högger, 2013) may be directly influenced by ABCG2 interaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These levels of bioavailable metabolites can exert modulatory effects in cells through selective actions on different components of the intracellular signaling cascades, which are vital for cellular functions such as growth, proliferation, and apoptosis (Crozier et al, 2009;Corsini et al, 2010). Therefore, the concentrations used in the present study (10 mm/l) are physiologically relevant (Corsini et al, 2010). In addition, the metabolism and tissue distribution of enterolactone as well as its enterohepatic circulation (Högger, 2013) may be directly influenced by ABCG2 interaction.…”
Section: Resultsmentioning
confidence: 99%
“…The metabolites of dietary phenolics, such as enterolignans, reach the systemic bloodstream in the range from nmol/l to low mmol/l concentrations. These levels of bioavailable metabolites can exert modulatory effects in cells through selective actions on different components of the intracellular signaling cascades, which are vital for cellular functions such as growth, proliferation, and apoptosis (Crozier et al, 2009;Corsini et al, 2010). Therefore, the concentrations used in the present study (10 mm/l) are physiologically relevant (Corsini et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 A recent investigation reported reductions in NFjB activation by enterolactone and enterodiol with decreased activation of downstream intracellular signaling targets involved in inflammation. 9 Further, it has been suggested that the transition from indolent tumor growth to more-aggressive tumor proliferation is accompanied by the onset of angiogenesis in a process coined, the angiogenic switch. 10 Thus, there is a rationale to hypothesize that therapies that inhibit angiogenesis would also exhibit anticarcinogenic properties.…”
mentioning
confidence: 99%
“…Phytoestrogens are superior in causing lower side-effects when administered for the treatment of illnesses (Gonzalez-Vallinas et al 2013;Hard and Edelstein 2015;Potocka et al 2013;Sharma et al 2014). Enterodiol (END) and enterolactone (ENL) are two important lignan-type phytoestrogens, which are associated with reduced risk of acute coronary events and many chronic diseases (Corsini et al 2010;Hu et al 2007;Sirotkin and Harrath 2014;Wang 2002). According to pharmacokinetics studies, high concentrations of END and ENL can be detected in the blood circulation after oral administration of…”
Section: Introductionmentioning
confidence: 99%